Measuring integration of agricultural markets - Traoré, Fousseini; Diop, Insa (International Food Policy Research Institute, 2021)
The study of market integration offers a powerful tool for understanding the relationships between geographically distant markets, for analyzing the impact of liberalization policies and for diagnosing the transmission of price shocks. The literature on tools for measuring market integration, particularly those developed for agricultural markets, has been subject to major developments in terms of approaches over the past two decades. This technical aims to provide an overview of the literature and tools for measuring agricultural markets integration, as well as their applications. The results should be interpreted with caution as these methods are in full development and must be linked to qualitative information that can support their validity.